PERANCANGAN BALANCE SCORECARD SEBAGAI INSTRUMEN PENGUKURAN KINERJA PADA CV. JADI JAYA MAKMUR SEMARANG - Prihasantyo Siswo Nugroho (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
Balanced Scorecard is a company performance measurement tool thatmeasures the performance of the company as a whole, both financially andnon-financial by using four perspectives, financial perspective, customerperspective, internal business perspective, and growth and learningperspective. Balance Scorecard assessment will be done at CV JADI JAYAMAKMUR Semarang.The first action plan that must be done by CV. So Jaya Makmur is toimprove service to consumers and provide the best service to maintaincustomer loyalty. With the highest gap value of -80% and relatively lowperformance, then the company really need to improve the best service tocustomer to maintain loyalty, such as bonus in the form of purchase discount,after sales service or hold gathering for special customers. The highest gaplies in the level of customer complaints, the percentage of purchases, the levelof machine efficiency per day, the timeliness of delivery and satisfactionsurvey and employee motivation. Therefore, our action plan is to improve thequality control of the production of goods, perform better productionplanning and make the delivery schedule more efficient.